The sundown syndrome: Will the specialized training of nurse's aides help elders with sundown syndrome? - Wallace, M. (Geriatric Nursing, 1994)
3 citations (Crossref) [2023-10-31]
Keywords: Aged; Humans; Nurses' Aides; Social Behavior Disorders; Time Factors; aged; article; dept.nur; human; nursing; nursing assistant; sociopathy; time

Nursing Diagnosis in Home Care: Audit Tool Development - Zink, M.R. (Journal of Community Health Nursing, 1994)
Little research has been done to document the value of using nursing diagnosis in home care and the impact that increased acuity levels have had in diagnostic selection. Nursing diagnosis documentation in home care was examined to see whether it had a relation to select client and visit pattern variables. This retrospective chart audit, which piloted a newly developed instrument called the Home Care Audit Tool, utilized a sample of 199 closed records of a large midwestem Visiting Nurse Association. The mean age of the client population was 76 years, with 64% female. There were 269 initial nursing diagnoses cited in the sample records, averaging 1.75 diagnoses per case. The number of recorded visits increased when select nursing diagnoses were cited together in a single case. © 1994, Taylor & Francis Group, LLC. All rights reserved.
5 citations (Crossref) [2023-10-31]
Keywords: Aged; Community Health Nursing; Female; Home Care Services; Human; Male; Models; Nursing; Nursing Audit; Nursing Diagnosis; Nursing Records; Pilot Projects; Reproducibility of Results; Retrospective Studies; Severity of Illness Index; article; community care; dept.nur; home care; medical assessment; nursing; nursing education

Nursing ethics committees —where are they? - Zink, M.R.; Titus, L. (Nursing Management, 1994)
When establishing Nursing Ethics Committees (NECs), statewide nursing organizations play an important role in developing and disseminating resources. The Connecticut Nurses Association Ethics and Human Rights Committee surveyed 85 healthcare facilities to identify active NECs. Representatives facilitated other committees by providing guidelines and assistance to those agencies developing NECs — the ultimate goal. © 1994 by Springhouse Corporation.
2 citations (Crossref) [2023-10-31]
Keywords: Bioethics and Professional Ethics; Clinical Approach/Source; Connecticut; Empirical Approach; Ethics Committees; Ethics Committees; Clinical; Ethics; Nursing; Human; Patient Advocacy; Questionnaires; Survey; United States; article; dept.nur; human; human rights; medical ethics; organization and management; professional standard; questionnaire; survey

Chaos theory and some nursing considerations - Vicenzi, Angela E (Nursing Science Quarterly, 1994)
The alleged synthesis of nursing and public health has not produced the expected community-as-client emphasis. Public health is characterized as disease-focused, with masculine domination, using a causal model. The explanatory model of chaos challenges nurses to reexamine nursing's theoretical base by questioning assumptions associated with linear thinking. The selected chaotic concepts of aperiodicity, attractors, sensitive dependence on initial conditions, phase space, and fractals are discussed here. Each concept's connection to physics and mathematics is cited and considerations for nursing science are outlined. Conclusions include redefining health, nursing, and community in chaotic terms and renaming nursing practice, which has this aperiodic and holistic paradigm, as ecologic health nursing.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/119-144-108-349-30X tex.type: [object Object]
Keywords: Chaos Theory; Community Health Nursing; Fractals; Human; Models; Nursing; Nonlinear Dynamics; Rogers; Thinking; article; dept.nur; fractal analysis; human; model; nonlinear system; nurse; thinking

Chaos Theory and Nursing Revisited: Commentary and Response - Zbilut, J.P.; Staffileno, B.; Vicenzi, A.E. (Nursing Science Quarterly, 1994)
3 citations (Crossref) [2023-10-31]
Keywords: Human; Nonlinear Dynamics; Nursing Theory; dept.nur; human; nonlinear system; note; nursing; ⛔ No DOI found

Social support systems in elder homebound clients - Zink, Margo R (Home Health Care Management & Practice, 1994)
An individual's social support system comprises multiple networks. A lack in one system may cause an increased need for support in another. Social support has been found to be of vital impor tance to the health of the older adult client and caregiver. It has been found to have a significant influence on health outcomes, acting as a buffer and altering recovery patterns. This article de scribes the concept of social support and relates how the home health care nurse can assess this dimension and use the findings to better plan patient care in the home setting. Key words: social support, home care, older adult. © 1994, Sage Publications. All rights reserved.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-578-813-060-298 tex.type: [object Object]
Keywords: dept.nur